The global Multidimensional Poverty Index (MPI) 2023 country results and methodological note - Alkire, S; Kanagaratnam, U; Suppa, N (Oxford Poverty and Human Development Initiative (OPHI), 2023)
This Methodological Note presents the methodology and technical decisions behind the country (national) results of the global Multidimensional Poverty Index (MPI) 2023. The 2023 MPI country results are based on the most recent data from 110 countries, covering 6.1 billion people.